TEOLOGI MUâTAZILAH: Sebuah Upaya Revitalisasi - Safii, Safii (TEOLOGIA, 2014)
Abstract: This article elaborates an important role in the history of Mutazila theology in Islamic World. Services that have been provided by this school seems to be forgotten by the Muslims, even it became despised and persecuted theology. In fact, this theology has made a large contribution indefending against attacks originating from the Jews, Christians, Zoroastrians, and Materialist. In the modern context, the spirit of this theology is relevant to be recalled that the freedom of thought as an integral part of the human being can grow and develop so that science and technology in the Islamic world can grow back. It must be recognized that this is indeed the flow had already given a negative image by traditional Islamic theology and hadith experts. Theology is imaged as a carrier of heresy.Abstrak: Artikel ini mengelaborasi peranan penting teologi Muâtazilah dalam sejarah Dunia Islam. Jasa-jasa yang telah diberikan oleh aliran ini tampaknya dilupakan begitu saja oleh umat Islam, bahkan ia menjadi teologi yang dimusuhi dan ditindas. Padahal, teologi ini sudah berjasa besar dalam melakukan pembelaan terhadap serangan-serangan yang berasal dari Yahudi, Kristen, Majusi, dan Materalis.Dalam konteks modern, spirit dari teologi ini relevan untuk di-munculkan kembali agar kebebasan berpikir sebagai bagian integral dari manusia dapat tumbuh dan berkembang sehingga sains dan teknologi di dunia Islam dapat tumbuh kembali. Memang harus diakui bahwa aliran ini memang sudah telanjur diberi citra negatif oleh teologi Islam tradisional dan ahli hadis.Teologi ini dicitrakan sebagai pembawa bidâah.Keywords: Muâtazilah, mihnah, Sunni, al-Quran, dan ahli hadis.